INTEGRATION OF CLOUD TECHNOLOGIES IN THE EDUCATIONAL SYSTEM (CAHIERS MAGELLANES-NS, 2024)
The integration of cloud technologies in the educational system represents a significant shift in how learning environments operate, offering new opportunities for collaboration, accessibility, and efficiency. This article explores the impact of cloud technologies on education, examining the benefits, challenges, and best practices associated with their adoption. Through an in-depth analysis of case studies and research findings, this study aims to provide insights into effective strategies for integrating cloud technologies into educational institutions.In recent years, cloud technologies have emerged as a transformative force in education, enabling innovative teaching practices and reshaping traditional educational models. This article investigates the integration of cloud technologies within educational settings, focusing on their potential to enhance teaching effectiveness, support personalized learning, and improve administrative efficiency.